How does thinking relate to tool making? - Malafouris, L (SAGE Publications, 2020)
How the boundaries of the mind should be drawn with respect to action and the material world is a core research question that cognitive archaeology shares with contemporary cognitive sciences. The study of hominin technical thinking, as in the case of stone tool making, is a good way to bring that question to the fore. This article argues that archaeologists who study lithic artefacts and their transformations over the course of human evolution are uniquely well positioned to contribute to the ongoing debate about the marks of the mental. Adopting the material engagement approach, I propose to replace the internalist vision of mentality, that is, the vision of a brain-bound mind that is using the body to execute and externalise preconceived mental plan through the stone, with an ecological-enactive vision of participatory mentality where bodily acts and materials act together to generate rather than merely execute thought processes. I argue that the latter participatory view changes the geography of the cognitive and offers a better description for the continuity of mind and matter that we see in the lithic record.